The concept heart as a fragment of language view of the world - Young Cheol Ko, Svetlana Yurievna Glushkova, Elvina Ilnurovna Khayarova, (Opción, 2019)
The study aims to investigate the concept "heart" as a fragment of language view of the world on the example of Bing Xin‟s poetry via the method of definitional and conceptual analysis. As a result, the heart in the language picture of the world of the writer is a place of concentration not only of emotions and feelings, but also of the mind and soul. In conclusion, the example of the functioning of the heart concept in the poetry of Bing Xin, shows its relevance of semantic and value elements for both individual and collective consciousness.